Les aventures du Sant Calze de Valence : quand la fiction se fait objet de foi et de mémoire - Sophie Albert (Perspectives Médiévales)
The article focuses the Santo Cáliz or, in Valencian, Sant Calze housed in the cathedral of Valencia (Spain). According to a legend elaborated in Aragon between the 11th and 14th centuries, the object, a 1st century vase mounted in a chalice during the Middle Ages, is supposed to be the cup by which Jesus established the Eucharistic rite at the Last Supper. While having structural similarities with the Arthurian Grail novels, the legend of the Sant Calze shows distinct issues: if not a literary motif, it is a material object, an object of faith and memory. It is part of a political and religious discourse that offers a christian-centered, monarchist and, in the 20th century, national-catholic vision of Spain history. The first part of the article describes the steps of the Sant Calze’s translatio and shows how the object has been taken up and invested by Franco’s ideology. The second part studies its modes of presence, its uses and its staging both in the cathedral of Valence and in the other places where it has been exhibited, moved or reproduced. The displacements, misappropriations, and manipulations of the Sant Calze shows how memorial discourses are staged and embodied or, here, reified.